DISCUSSION GUIDE FOR THE PREPARATION OF A VISITOR MANAGEMENT PLAN FOR THE SPECIAL REGION OF YOGYAKARTA - Aisyah Astinadia Siregar (Jurnal Abdisci, 2024)
Tourism development is a significant and strategic thing for regional growth. DIY is a popular tourist destination with various elements that continue to develop to attract visitors. The purpose of the implementation of the DIY Tourism Visitor Management Plan Preparation activity is to collect information on tourism products from various parties and dialogue with stakeholders to design a tourism visitor management plan in the region. The purpose of Community Service Activities with the Preparation of Visitor Management Plans in Yogyakarta is to achieve structured visitor management in the Special Region of Yogyakarta. The heads of the DIY tourism office, hotel, restaurant, and tourist attraction managers gave a positive response to the guidelines for discussing the visitor management plan in the Special Region of Yogyakarta. Arousing the interest of tourists, both domestic and foreign, by creating a safe, comfortable, and secure environment for visitors to tourist sites in Yogyakarta.